Managerial accounting - Hilton, Ronald W. (New York : McGraw-Hill, 1991)
This text combines traditional material with up-to-date coverage of emerging topics in managerial accounting. It discusses the importance of such innovations as just-in-time inventory systems, flexible manufacturing and computer-integrated manufacturing accounting systems.
Includes bibliographical references and indexes.
oif 18/03/15
Loan
Keywords: Managerial accounting; Management accounting